REGULASI OSMOTIK DAN NILAI HEMATOKRIT IKAN NILA (Oreochromis sp.) PADA MEDIUM DENGAN SALINITAS DAN TEMPERATUR AIR BERBEDA - Untung Susilo; Wahyu Meilina; Sorta Basar Ida Simanjuntak (The East Java Biological Society, 2012)
Osmotic regulation and blood hematocrite of nile, Oreochromis sp., have been evaluated as response to different salinity and water temperature. Three different salinities (0 ppt, 10 ppt and 20 ppt) in combination with two different water temperatures (26° C and 30° C) have been applicated in this experiment. Fish with average body weight 28.3 ± 2.62 g were used ini this experiment. The result showed that plasma osmolality of nile in freshwater have not different with in 10 ppt (P > 0.05), but plasma osmolality increased at 20 ppt especially at 8,16 and 24 hours after aclimated on 20 ppt. Osmoregulatory capacity has signifi cant heigher (P < .05) on nile in freshwater than in water with salinity 10 ppt and 20 ppt. Body water content and blood hematocrite were not signifi cant between different salinity and water temperature (P >.05). Conclution, osmotic regulation of nile showed signifi cant different between salinity treatment, but blood hematocrite only changed at 8,and16 hours after nile aclimated on water salinity 20 ppt and body water content not changed at both diferent salinity and water temperature.